Immune-Related Adverse Events Associated With Immune Checkpoint Inhibitors for Advanced Non-small Cell Lung Cancer: A Network Meta-Analysis of Randomized Clinical Trials - Zhang, Weidong; Gu, Jingjing; Bian, Chunming; Huang, Guanhong (Frontiers in Pharmacology, 2021)
Objective: This network meta-analysis will provide a complete toxicity profile, and safety ranking of programmed cell death receptor 1 (PD-1) and its ligand, programmed cell death ligand-1 (PD-L1) inhibitors for treatment of advanced non-small cell lung cancer(NSCLC). Methods: We found 12 phase II or III randomized clinical trials (RCTs) including 8,453 patients with NSCLC by searching Pubmed, Embase, and ClinicalTrials.gov. Risk ratios(RRs) and 95% confidence interval(CI) were used to compare the rate of irAEs for different PD-1/PD-L1 inhibitor-based treatments using network meta-analysis with random effects model. Results: For dermatologic irAEs, the corresponding ranking of incidences of the seven groups from low to high was: platinum-based chemotherapy(4.7%), durvalumab(17.5%), atezolizumab+platinum(39.9%), pembrolizumab+platinum(43.3%), nivolumab(67.1%), pembrolizumab(80.1%), nivolumab+ipilimumab(97.4%). For colitis, the corresponding ranking of incidences of the seven groups from low to high was: platinum-based chemotherapy(8.5%), pembrolizumab+platinum(41.4%), durvalumab(45.2%), pembrolizumab(60.5%), nivolumab(67.3%), atezolizumab+platinum(77.1%). For endocrine irAEs, the corresponding ranking of incidences of the seven groups from low to high was: platinum-based chemotherapy(0.3%), pembrolizumab+platinum(33.5%), nivolumab(45.7%), atezolizumab+platinum(60.4%), pembrolizumab(61.9%), durvalumab(69.1%), nivolumab+ipilimumab(79.1%). For pneumonitis, the corresponding ranking of incidences of the seven groups from low to high was: atezolizumab(13.3%), platinum-based chemotherapy(18.1%), nivolumab(35.9%), atezolizumab+platinum(56%), durvalumab(62.2%), pembrolizumab+platinum(65.1%), pembrolizumab(99.3%). For hepatitis, the corresponding ranking of incidences of the six groups from low to high was: platinum-based chemotherapy(9.8%), nivolumab(44.5%), atezolizumab+platinum(53.8%),durvalumab(56.4%), pembrolizumab+platinum(64.3%) pembrolizumab(71.2%). Conlusions: In addition to platinum-based chemotherapy, durvalumab for dermatologic and liver irAEs, pembrolizumab for gastrointestinal irAEs, pembrolizumab+platinum for endocrine irAEs, and atezolizumab for pneumonitis may be associated with lower rates of irAEs than other immune-based regimens. Nivolumab+ipilimumab for dermatologic and endocrine irAEs, atezolizumab+platinum for colitis, and pembrolizumab for pneumonitis and hepatitis may be associated with higher rates of irAEs.